Elementary School Students’ Interest in Learning Citizenship Education - Fadhilatul Husna (International Journal of Students Education, 2024)
This study aim for analyze interest study elementary school students moment using wordwall media in Citizenship Education (PKn) learning. Citizenship education in schools basics are also purposeful for develop attitude good social, moral and ethical behavior in students. They taught for become responsible individual answer, care to environment around, and capable interact in a way positive with fellow. Method used is is review literature systematic. A total of 5 articles have been published published accordingly with theme as answer in this study. Research result show a number of aspect in environment education can influence development interest learning, which is component important from this process. as well as learning media is one of possible factors influence interest study student elementary School. Personal interests also arise moment somebody enjoy something activities, which encourage ongoing and more engagement deep in the learning process. Utilise various types of learning media and approaches creative in convey information can help guard interest student still stay awake and avoid boredom.